Literacy and Knowledge of Financial Behavior - Indrawati Mara Kesuma; Ronal Aprianto; Nora Puspita; Suyadi Suyadi; Suwarno Suwarno; Weni Susanti (UNIVED Press, 2024)
The purpose of this study was to analyze and measure the effect of financial literacy and financial knowledge on financial management behavior in active students of private universities in Lubuklinggau City. The total population in this study was 8,071 students and the sample technique used was random sampling using the slovin formula. Data was collected using a questionnaire method from 381 students who were the sample in this study. The data analysis technique used in this research is descriptive statistical analysis, data quality test, classical assumption test (outer model and inner model) with the help of the PLS version 3.0 software program. The results of this study indicate 1) that financial literacy has a negative and significant effect on financial management behavior in active students of private tertiary institutions in Lubuklinggau City with a statistical value showing a number of 1.600 which is <1.96 and it can also be proven that the P values ​​are 0.110 or called more greater than 0.005 2) that financial knowledge has a positive and significant effect on financial management behavior in active students of Lubuklinggau City Private Higher Education with a statistical value showing a number of 14.446 which is> 1.96 and it can also be proven that the P Values are worth 0.000 or are called smaller of 0.005 and 3) that financial literacy and financial knowledge have a positive effect on financial management behavior in active students of private universities in Lubuklinggau City. This is evidenced by the R-Square value of 0.628.